Phosphoenolpyruvate carboxylase identified as a key enzyme in erythrocytic Plasmodium falciparum carbon metabolism. - Janet Storm; Sonal Sethia; Gavin J Blackburn; Achuthanunni Chokkathukalam; David G Watson; Rainer Breitling; Graham H Coombs; Sylke Müller (PLoS Pathogens)
Phospoenolpyruvate carboxylase (PEPC) is absent from humans but encoded in the Plasmodium falciparum genome, suggesting that PEPC has a parasite-specific function. To investigate its importance in P. falciparum, we generated a pepc null mutant (D10(Δpepc) ), which was only achievable when malate, a reduction product of oxaloacetate, was added to the growth medium. D10(Δpepc) had a severe growth defect in vitro, which was partially reversed by addition of malate or fumarate, suggesting that pepc may be essential in vivo. Targeted metabolomics using (13)C-U-D-glucose and (13)C-bicarbonate showed that the conversion of glycolytically-derived PEP into malate, fumarate, aspartate and citrate was abolished in D10(Δpepc) and that pentose phosphate pathway metabolites and glycerol 3-phosphate were present at increased levels. In contrast, metabolism of the carbon skeleton of (13)C,(15)N-U-glutamine was similar in both parasite lines, although the flux was lower in D10(Δpepc); it also confirmed the operation of a complete forward TCA cycle in the wild type parasite. Overall, these data confirm the CO2 fixing activity of PEPC and suggest that it provides metabolites essential for TCA cycle anaplerosis and the maintenance of cytosolic and mitochondrial redox balance. Moreover, these findings imply that PEPC may be an exploitable target for future drug discovery.